Manejo del Botiquín de Primeros Auxilios en el Aula de Inicial 1 de la Unidad Educativa Miguel Ángel León Pontón, Cantón Riobamba. - Criollo Toapanta, Tannia Elizabeth (2025)
The objective of this research entitled; management of the first aid kit in the first grade classroom, is to analyze the correct management of the first aid kit located in the first grade classroom of the Miguel Ángel León Pontón Educational Unit, Canton Riobamba, through the information of its content to provide adequate and timely care in case of emergency providing safety to children. In order to better understand the research topic, a methodology with a qualitative approach was carried out with a bibliographic approach where searches were conducted in different books, magazines and academic articles, a field approach because it was done directly in the educational environment, and a cross-sectional approach where data is collected at a specific time, with a non-experimental design, in which information was collected to reach a correct analysis allowing to highlight different strategies that can help to work with children, in terms of knowledge of the elements of the first aid kit. We worked with a population of 22 children of initial education 1, where an observation sheet was used, in which information was obtained to carry out the respective tabulation, analysis and interpretation, in the results it was evidenced that during the education process strategies are not frequently carried out for the adequate knowledge and identification of the elements of the first aid kit.